Existential vulnerability and transition: Struggling with involuntary childlessness on Instagram - Stenström Kristina; Pargman Teresa Cerratto (Nordicom Review)
In their efforts to find others who share their experiential reality and existential struggle, many involuntarily childless women turn to Instagram to engage and participate in the practice of trying-to-conceive (TTC) communication. Through the conceptual lens of digital existence, where the digital and online are regarded as constitutive of existential transition, we draw on ten interviews and an online ethnography to explore some of the struggles that involuntarily childless women experience with and through technology. We find that TTC communication can be constitutive of coming to terms with the status of involuntary childlessness. In particular, this study illustrates that TTC communication, for involuntarily childless women, is both a site of struggle and a safe space as they transition to nonmotherhood in an existential terrain where they share an intimate journey.